All Things New : the Trinitarian Nature of the Human Calling in Maximus the Confessor and Jurgen Moltmann - Bingaman, Brock (Princeton theological monograph series, 2015)
For both Maximus the Confessor (c. 580-662) and Jurgen Moltmann (b. 1926) understanding what it means to be human springs from a contemplative vision of God. This comparative study explores surprising parallels between the theological anthropology of the seventh-century Byzantine monk and the contemporary German Protestant. Bingaman shows that Maximus and Moltmann root their understanding of the human calling in their Trinitarian and christological reflection, in contrast to many modern theologies that tend to devise an account of human being first, and then try to find ways in which Christ an.